2018
DOI: 10.26442/terarkh201890104-39
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphic markers in candidate genes and the risk of manifestationof endocrine ophthalmopathy in patients with Graves’ disease

Abstract: Aim. To analyze the association between the polymorphic markers in CTLA4, TNF, IL10 and IL16 genes and the risk of manifestation of endocrine ophthalmopathy (EO) in patients with Graves’ disease (GD). Materials and methods. Case-control study included 248 patients with GD. Using polymerase chain reaction we studied the distribution of alleles and genotypes of polymorphic markers such as A60G (rs3087243) in CTLA4 gene, G(-308)A (rs1800629) in TNF gene, G(-1082)A (rs1800896) in IL10 gene, T3249C (rs4778641) in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Data on PAI-1 polymorphisms in TED, up till now, have not been published, and only few candidate other genes have been studied in this respect. CTLA-4, 27 vitamin D receptor, 28 TNF, IL-10 29 and deiodinase-2 polymorphisms 30 were recently described in patient cohorts of comparable size. However, unlike these genes which are immune response related, PAI-1 acts on the other side of the orbital process, stabilizing the extracellular matrix and facilitating its expansion, which explains nearly all signs and symptoms of TED.…”
Section: Discussionmentioning
confidence: 95%
“…Data on PAI-1 polymorphisms in TED, up till now, have not been published, and only few candidate other genes have been studied in this respect. CTLA-4, 27 vitamin D receptor, 28 TNF, IL-10 29 and deiodinase-2 polymorphisms 30 were recently described in patient cohorts of comparable size. However, unlike these genes which are immune response related, PAI-1 acts on the other side of the orbital process, stabilizing the extracellular matrix and facilitating its expansion, which explains nearly all signs and symptoms of TED.…”
Section: Discussionmentioning
confidence: 95%
“…We found that those GD-related SNPs were located at different positions in the CTLA4 region within different populations. The majority of patients with GD from different ethnicities were associated with rs231775 and/or rs3087243 (Polish [37,38], Chinese [39,40,41,42,43,44], Saudi Arabian [45,46], Iranian [47,48], Italian [49], Japanese [50], and Taiwanese [17,18,19]). However, rs733618 and its relationship with GO have been found merely in Taiwan population.…”
Section: Discussionmentioning
confidence: 99%